IGREJA UNIVERSAL DO REINO DE DEUS: MEMÓRIA E RELIGIÃO NO TEMPLO DE SALOMÃO - JECOV, WILSON FLÁVIO (2017)
The Temple of Solomon – the largest religious space built by the IURD (Universal Church of the Kingdom of God) in our city between 2010 and 2014, is the object of our analysis based on the relationship between Memory and Religion, of Memory and the Memory of Place. Now as the Place of the Memory of the Religion of this contemporary Pentecostal institution, now as the Memory of Religious Places, the spaces related to the Abrahamic monotheistic religious culture (Judeo-Christian), reproduced by her in the neighborhood of Brás: The Tabernacle of the Desert, the Garden of Olives, the Memorial (Historical Cultural Museum) and the Temple of Solomon and its Sanctuary. Except for the Tabernacle of the wilderness, all of them related to the city of Jerusalem which is known as the holy city. Our studies have combined two methodologies: bibliographic research (theory) related to authors related to Geography, Geography of Religion, Sociology of Memory and the history of the Universal Church, constituting the two important concepts of our research: Memory of Religion and Religious Tradition, as both are products of our society. And our field work (urban geography), with observatory visits to three religious spaces of this denomination: the Temple of Solomon (Brás), the Universal Cathedral in São Caetano do Sul (central) the common church located on the outskirts of East Zone (Vila Diva), and in other denominations belonging to contemporary Pentecostalism in Brás around the Temple of Solomon And in other suburban neighborhoods in the East Zone of the city, perceiving Pentecostal pluralism in the religious field of São Paulo.